ANALISIS PENGARUH BRAND PERCEIVED VALUE AWARENESS, PERCEIVED QUALITY TERHADAP LOYALITAS PELANGGAN PADA PRODUK BUMBU MASAK KOKITA DI KOTA BATAM - Yuda Riskiawan; Edwin Agung Wibowo; Yannik Ariyati (EQUILIBIRIA, 2017)
This thesis entitled "Analysis of Effect of Brand Awareness, Perceived Value, Perceived Quality on customer loyalty seasoning products Kokita in Batam". The purpose of this study was to determine the influence of implementation of the increase in brand value and quality of the products seasoning in Batam. Data collected through questionnaires and conducted on 89 respondents. Analysis of the data in this study using SPSS version 20. The sample statistical technique or by using formula slovin study estimates the error rate of 10% and testing techniques of data used in this study include test validity by factor analysis, reliability tests with Cronbach Alpha , Classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis. Hypothesis testing using t test showed that the variable Brand awarenes, variable effect on customer loyalty, perceived value, and the effect on customer loyalty Perceived quality variable effect on customer loyalty. Then through the F test showed that the three independent variables simultaneously affect the customer loyalty. Figures Adjusted R2 of 0.940 indicates that 94% variable Loyalty can be explained by the three independent variables in the regression equation, while the remaining 6% is explained by other variables outside the three variables used in the study